(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2023)
This article discusses the teaching of the discipline of chemistry to students of construction engineering specialties. Studying this course will help to form and develop students’ intellectual abilities in the field of chemistry and experience in their application. The combination of traditional teaching methods with mini-research is aimed at the formation of chemical concepts, research skills, and the improvement of professional competencies.